2021
DOI: 10.3389/fmars.2021.760909
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ecological Accommodation Space and Sediment Supply for Cold-Water Coral Mound Formation, a Case Study From the Western Mediterranean Sea

Abstract: The formation of cold-water coral (CWC) mounds is commonly seen as being the result of the sustained growth of framework-forming CWCs and the concurrent supply and deposition of terrigenous sediments under energetic hydrodynamic conditions. Yet only a limited number of studies investigated the complex interplay of the various hydrodynamic, sedimentological and biological processes involved in mound formation, which, however, focused on the environmental conditions promoting coral growth. Therefore, we are stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Of all paleoenvironmental parameters considered here, only the grain-size data used as a proxy for the hydrodynamic setting can be directly affected by the distance between the off-mound site and the coral mound site. However, even though coral mounds (being able to accelerate local currents due to their elevated topography, e.g., [ 62 ]) and thriving coral reefs on their top (being able to decelerate local currents due to the baffling effect of the coral framework, e.g., [ 63 ]) may induce local effects, their ability to modulate the regional current regime is limited. Hence, the regional hydrodynamic setting is best recorded in the off-mound records that are generally unaffected by local coral mound-related effects.…”
Section: Methodsmentioning
confidence: 99%
“…Of all paleoenvironmental parameters considered here, only the grain-size data used as a proxy for the hydrodynamic setting can be directly affected by the distance between the off-mound site and the coral mound site. However, even though coral mounds (being able to accelerate local currents due to their elevated topography, e.g., [ 62 ]) and thriving coral reefs on their top (being able to decelerate local currents due to the baffling effect of the coral framework, e.g., [ 63 ]) may induce local effects, their ability to modulate the regional current regime is limited. Hence, the regional hydrodynamic setting is best recorded in the off-mound records that are generally unaffected by local coral mound-related effects.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, significant environmental changes on the continental slope decrease onshore sediment inputs to the continental slope due to landward migration of the coastline [6,92,93]. Hence, the mounds could be controlled by changes in the sediment focusing, resulting in lateral sediment supply and changing deposition on the mounds, as supported in [53] and also changes in the current bottom-current regimes. Considering all these observations, it is possible that changes in the water mass circulation and water column structure, productivity, near-bottom currents and sediment supply may also have induced the demise of the studied northern Alboran Sea mounds as detected in the southern Alboran Sea CWC mounds.…”
Section: Potential Main Framework-building Organisms Of the Moundsmentioning
confidence: 99%
“…The bottom sediments and associated benthic communities on the mounds are similar to those detected on the seafloor adjacent to the mounds, indicating a very low present-day benthic heterogeneity between the studied mounds and the surrounding seabed. Generally, mound formation requires mound growth to be faster than background sedimentation, and baffling of hemipelagic sediment is a major component contributing to mound growth (especially in branching mound-forming organisms; [5,18,20,33,34,53]. Thus, the burial of carbonate mounds appears to be a consequence of the cessation of active reefs and, thus, mound growth induced by the deterioration of living conditions for the respective mound-forming organisms [5].…”
Section: Current and Past Sedimentary Environment Affecting The Mound...mentioning
confidence: 99%
See 1 more Smart Citation
“…Within the EMCP, the localities of Brittlestar Ridge I (BRI) and Dragon Mound have received the most attention during the last decade (Fig. 1b and c; Fink et al, 2013Fink et al, , 2015Stalder et al, 2015Stalder et al, , 2018Terhzaz et al, 2018;Fentimen et al, 2020a;Krengel, 2020;Rachid et al, 2020;Wang et al, 2021). U-series dating of corals revealed that the formation of Dragon Mound began 450 kyr ago, whereas BRI started building up over 538 kyr ago (Krengel, 2020).…”
Section: Introductionmentioning
confidence: 99%